Can we effectively allocate time for work and life and be happy? The empirical evidence from self-employed persons in Lithuania - Viktorija Tauraitė (Ekonomika, 2024)
There is not enough attention paid to the analysis of time allocation in the context of happiness. Perhaps it is because happiness economics is an expanding interdisciplinary field. So, recommendations for self-employed persons in Lithuania how daily time should be effectively allocated for life (sleep, personal care, study, housework, family care, leisure, travel and other activities) and work in order to be happy still remain an open question. In this paper the specific recommendations about it are provided for that case. So, this paper analyses two phenomena, i.e. time allocation and happiness. The main attention is given to self-employed persons in Lithuania during 2019 years. Data collection (time diary, survey, interview) and optimization meth-ods are used to identify how daily time should be effectively allocated for two main areas (work and life) in order for self-employed persons to be happy. Having mathematical modeling of time allocation and happiness accomplished, it has been found that 36.1% of day time should be allocated for work and the rest time of the day (63.9%) should be allocated for life. The person's levels of job satisfaction, life satisfaction and happiness should be equal to 9 points (on a ten-point scale). In this case, monthly net income would be 1001 euros and desirable monthly net income 1101 euros. The number of children should be two. The scientific and practical uniqueness of this article lies in the creation of a mathematical model that can determine how to effectively allocate work time and life time in order for a person to be happy. Although the mathematical model constructed in this paper is based on Lithuanian data, it is not country specific.
Keywords: 330; time allocation; happiness; self-employed persons; work-life balance